Managing Nature 5.0 in Industrial Revolution 4.0 and Society 5.0 Era - Mohammed Ali Berawi (International Journal of Technology, 2019)
Advances in technology have led to more production of environmental friendly projects, products and services. As our colleagues from Germany and Japan highlight the importance of Industry 4.0 and Society 5.0, and after a series of my previous notes on technology and sustainable development, I would like now to extend our discussion on how the latest technology can be a powerful mechanism to improve our standard of living and sustain our mother earth. Industry 4.0 emerged from innovative digital technology to create value creation, whilst Society 5.0 is argued as a human-centered society that balances economic advancement with Industry 4.0. On the other hand, the environment has provided us with natural resources that speed up the growth of our industries and economies towards sustainability.